Synthesis and characterisation of strong hydrophobic bentonite. (19th September 2015) - Huang, W.; Wang, Y.; Qiu, Z.; Leong, Y.-K.; Cui, M.; Zhong, H.
Abstract : In the preparation of a hydrophobic bentonite, the clay was first purified and then converted to sodium form with sodium fluoride before being made hydrophobic by intercalation with octadecyl dimethyl phenylmethyl ammonium chloride (ODPAC). Elemental and mineral compositions of the sodium-modified bentonite were determined using X-ray fluorescence spectrometry (XRF) and X-ray diffraction (XRD). The swelling capacity and colloid index were also determined. For the hydrophobic bentonite, the following were characterised microstructure, interlamellar spacing, composition, thermal stability, wettability, surface energy and dispersity using a range of techniques: SEM, XRD, FTIR, thermogravimetric analysis (TGA) and contact angle. The colloid fraction and rheological properties were also determined. Sodium modification caused a certain increase in clay and Na2 O contents and decrease in quartz content. The interlamellar spacing was also decreased to 10.03 Å. Hydrophobic bentonite displayed a larger interlamellar spacing of 18.73 Å confirming that intercalation by the surfactant has occurred. The hydrophobic bentonite particles displayed a thick flat layered morphology. It displayed high thermal stability with the organic modifier (ODPAC) decomposition occurring at a temperature higher than 260°C. It is much more hydrophobic and has a smaller surface energy than sodium bentonite. It dispersed easily in white oil 5#, white oil 7# and synthetic base causing an increase in viscosity and yield point as intended.